AFFECT IN ORGANIZATION AND MANAGEMENT - Hunter, Carolyn, 1984-; Kivinen, Nina, 1974- ([S.l.] : ROUTLEDGE, 2022)
Affect in Organization and Management asks how affect theory understands everyday working lives through embodied, social and political practice. Discussing a range of dimensions and perspectives on affect, the book considers how subjects are formed through their connections with others, both human and non- or more-than-human. The six women writers on affect presented in this series (Sara Ahmed, Kathleen Stewart, Donna Haraway, Jane Bennett, Karen Barad and Rosalyn Diprose) all speak to important themes in organization studies, including power, politics and ethics. Each chapter explores how these thinkers have already influenced organization scholars, as well as how their work can extend our understanding of pressing organizational issues around gender, race, the environment, leadership and ethics. Feminism is a core feature of this collection, highlighting feminist writing with affective, connected and intersubjective possibilities. Each woman writer is introduced by experts on affect and organization studies. The chapters also suggest further reading and accessible resources. The book is suitable for students, academics and practitioners in business and management, organization studies and critical management studies who want to think differently about organizations.
Keywords: Affect (Psychology); Psychology, Industrial; Organizational behavior; BUSINESS & ECONOMICS / Organizational Behavior; BUSINESS & ECONOMICS / Business Ethics